Accounting for goodwill - Han, Alvin Cheung Shiong (2015)
Despite the development in accounting theory and the substantial amount of literature that has been written, a common prescribed method for the accounting of goodwill has still not been identified. This has resulted in a potpourri of accounting methods, practised by accounting practitioners the world over. In a bid to harmonise these global practices, the International Accounting Standards Committee (IASC) has issued the Exposure Draft (ED 32) to reduce the number of acceptable goodwill accounting practices. Against this background, this study was undertaken in the form of a postal questionnaire survey to: (i) investigate the extent of goodwill accounting practices, and the impact of ED 32 on companies in Singapore. (ii) test the hypothesis as to whether managers of companies in Singapore utilise goodwill accounting practices to influence earnings.